PHYTOCHEMICAL ANALYSIS OF STROBILANTHES BLUME SPECIES FROM NORTHERN WESTERN GHATS OF INDIA - Fernandes, Maria Cineola; Sellappan, Krishnan (International Journal of Current Pharmaceutical Research, 2016)
Objective: The chief phytoconstituents in ten Strobilanthes species of both leaf and stem were identified in order to relate the presence of biological and pharmacological activities. Methods: Strobilanthes species were collected from Northern Western Ghats of India and phytochemicals such as alkaloids, carbohydrates, glycosides, saponins, proteins, phytosterols, terpenoids, fixed oils, phenolics and flavonoids were analyzed using standard methods. Results: Strobilanthes species of both leaf and stem showed the presence of terpenoids, flavonoids, phytosterols, phenolic compounds, fixed oils, carbohydrates. Terpenoids and phytosterols are also present in all species of Strobilanthes. On the other hand, phenolics, carbohydrates, flavonoids are found in most of the species of Strobilanthes. In addition, alkaloids, glycosides, saponins, proteins, fixed oils are found some species of Strobilanthes. Among the species studied, the stem of S. integrifolius, S. ixiocephalus, S. reticulatus var. reticulatus, Strobilanthes Blume sp. and leaf of S. lupulinus, S. barbatus showed the absence of alkaloids. Glycosides were present only in S. ciliatus (leaf), S. callosus (stem) and S. heyneanus (stem). Saponins were found in S. ciliatus (leaf), S. ixiocephalus (leaf, stem), S. callosus (leaf) and leaf and stem of S. heyneanus. Proteins were found only in the stem of S. callosus and S. sessilis var. ritchiei. Fixed oils also are known as carrier oils were moderately found in the Strobilanthes species. Conclusion: Thus, the detection of phytochemical constituents in ten Strobilanthes species is important in interpreting the medicinal properties and pharmacological value of the species.